(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Using Lattice Boltzmann Method (LBM), the mixed convection and surface radiation effect in a two-sided lid-driven square cavity is studied numerically with air as a working fluid. The numerical code is validated against results available in the literature. The parameters governing the problem are the emissivity of the walls, the Reynolds number and the Richardson number that was varied through the Grashof number. The results obtained show significant effects of the Richardson number and surface radiation on the overall structure of the flow and heat transfer characteristics. The contribution of radiation component to the total Nusselt number outclasses that of convection for high emissive walls at some threshold value of Richardson number.